A trade‐off between quantity and quality of offspring in haematophagous ectoparasites: the effect of the level of specialization. (23rd September 2013) - Khokhlova, Irina S.; Pilosof, Shai; Fielden, Laura J.; Degen, A. Allan; Krasnov, Boris R.; Cotter, Sheena
Summary Theory predicts an adaptive trade‐off between quantity and quality of offspring if mothers can reliably predict the offspring environment. We studied egg production and quality of offspring in two flea species (host‐specialist Parapulex chephrenis and host‐generalist Xenopsylla ramesis) exploiting eight rodent species. We evaluated quality of new imagoes via their developmental time, size (length of a femur as a proxy) and resistance to starvation without a blood meal. We predicted that the offspring quality would increase with (i) a decrease in the number of eggs produced by mothers and (ii) an increase in phylogenetic distance between maternal host and principal host of a flea. We also predicted that negative relationships between offspring quality and either maternal egg production effort or phylogenetic distance between maternal host and the principal host or both would be manifested stronger in host‐opportunistic than in host‐specific fleas. The highest number of eggs produced per female flea was accompanied by the longest duration of development and the smallest offspring in X. ramesis, while P. chephrenis that hatched from larger clutches survived for less time under starvation. Although there was no significant effect of host species on any dependent variable, association between offspring quality and phylogenetic distance of the maternal host from the principal host of a flea was found in X. ramesis (but not P. chephrenis) with new imagoes being larger if their maternal hosts were phylogenetically distant from the principal host. Our results demonstrated stronger trade‐off between quantity and quality of offspring in a generalist than in a specialist flea, supporting the association between life‐history plasticity and generalist feeding strategy.